Bài 1.
Cho a+b+c=0. Tính:
\(\frac{1}{a^2+b^2-c^2}+\frac{1}{b^2+c^2-a^2}+\frac{1}{c^2+a^2-b^2}\)
Bài 2.
Cho a-b-c=0. Tính:
\(\frac{1}{a^2+b^2-c^2}+\frac{1}{b^2+c^2-a^2}+\frac{1}{c^2+a^2-b^2}\)
Bài 3. Cho \(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}=0(a,b,c\ne0)\)
Rút gọn: \(\frac{bc}{a^2+2bc}+\frac{ca}{b^2+2ac}+\frac{ab}{c^2+2ab}\)
Bài 4. Cho \(\left(a+b+c\right)^2=a^2+b^2+c^2\)
Rút gọn:\(\frac{a^2}{a^2+2bc}+\frac{b^2}{b^2+2ac}+\frac{c^2}{c^2+2ab}\)
1. a + b + c = 0 \(\Rightarrow\)a + b = -c \(\Rightarrow\)( a + b )2 = ( -c )2 \(\Rightarrow\)a2 + b2 - c2 = -2ab
Tương tự : b2 + c2 - a2 = -2bc ; c2 + a2 - b2 = -2ac
Ta có : \(\frac{1}{a^2+b^2-c^2}+\frac{1}{b^2+c^2-a^2}+\frac{1}{c^2+a^2-b^2}\)
\(=\frac{1}{-2ab}+\frac{1}{-2bc}+\frac{1}{-2ac}=\frac{-1}{2}\left(\frac{1}{ab}+\frac{1}{bc}+\frac{1}{ac}\right)\)
\(=\frac{-1}{2}\left(\frac{a+b+c}{abc}\right)=0\)
2. tương tự
3,4 . có ở dưới, câu hỏi của Quyết Tâm chiến thắng